USING VERTICAL GARDENING TO IMPROVE THERMAL INSULATION IN URBAN CONDITIONS - Lytvyn, Bohdan Bohdanovych; Kosyk, Oksana Ivanivna (Theory and practice of design, 2023)
The purpose of this work is to emphasize the importance of thermal insulation in the conditions of a modern city and to offer a more natural alternative to existing materials. The constant growth of the urban population leads to an increase in the demand for housing. Young people move to cities for new opportunities, which leads to increased energy consumption, which has a direct negative impact on the environment. This endless cycle is mostly about efficiency. Improving the thermal properties of each house will make it possible to create an economically efficient system suitable for use in all existing housing, we would achieve a great percentage of saved money on heating and cooling, as well as reduce our dependence on fossil fuels, which in turn allows to save much more on infrastructure, specified equipment and subsidies for this industry. This research employs a comprehensive methodology by analyzing existing works on urban «heat island» effect and it`s mitigation, as well as data on creating a more sustainable water management systems and examples of using vertical gardening in construction for both newly built and existing housing. The results of the study illustrate the significant improvements in thermal insulation that can be achieved by integrating vertical gardens into urban structures. Through a combination of experimental data and existing implementations, it has been observed that the presence of vertical gardens leads to a noticeable increase of heat insulation. These results highlight the potential of incorporating vertical gardens as a sustainable solution to enhance the thermal performance of urban buildings. This scientific novelty of this research contributes to the scientific literature by offering a new perspective on the role of vertical gardening in urban thermal insulation. The identification of optimal plant species and configurations for specific urban contexts adds a new dimension to sustainable urban design, emphasizing the importance of green infrastructure in addressing contemporary environmental challenges. The practical implications of this research are substantial for architects, urban planners, and policymakers. The findings provide actionable insights into leveraging vertical gardening as a sustainable strategy to reduce energy consumption, retrofit existing buildings to meet the criteria for sustainable housing and mitigate the urban «heat island» effect.